Analisis Faktor Yang Mempengaruhi Minat Berwirausaha Mahasiswa Institut Teknologi Indonesia - Puspita, Mutiara eka; Tampubolon, Edward Sahat; Marpaung, Fredric MH (Emerging Markets : Business and Management Studies Journal, 2022)
This research aims to measure entrepreneur personality, entrepreneur knowledge, and family environment on entrepreneurial interest from college student Institute technology of Indonesia. The research problem is finding the influence of potential entrepreneur personality entrepreneurial knowledge and family environment on entrepreneur’s interest. This research uses a quantitative approach. The population is the institute technology of Indonesia student with sample determinated use a purposive sampling technique because student not known certainty number interest entrepreneurship. Data were collected with a questionnaire instrument for validity and reliability using SPSS. Classic assumption test was first performed as a prerequisite for analysis multiple linear. Definitive assumption results obtained that data are normally distributed, multicollinearity and heteroscedasticity do not occur. Results of the regression analysis prove that simultaneously, personality, knowledge, and family environment variables influence the interest of ITI student entrepreneurs. However, partially, only personality and family environmental variables influence interest entrepreneurship. The magnitude of the coefficient of determination is 62.3%, meaning that there are 37.7% other variables not included in this study that also affect ITI students’ interest in becoming an entrepreneur.